The temperature‐dependent ballistic performance and the ductile‐to‐brittle transition in polymer networks. Issue 9 (19th March 2019) - Masser, Kevin A.; Long, Tyler R.; Yu, Jian H.; Knorr, Daniel B.; Hindenlang, Mark D.; Taylor, Terrence; Harris, Doug; Lenhart, Joseph L.
ABSTRACT: The temperature dependence of the ballistic impact performance of a series of transparent polymer networks is evaluated. A systematic series of homogeneous epoxy/propylene‐oxide‐based thermosets, a nanoscale phase‐separated epoxy/dual amine thermoset, and two homogeneous, completely aliphatic materials synthesized via ring‐opening metathesis polymerization are examined. The Vogel temperature ( T o ) and the Kauzmann temperature ( T K ) are critical parameters for scaling the temperature‐dependent ballistic impact performance of each class of materials. The ductile‐to‐brittle transition temperature in a series of propylene‐oxide amine‐cured epoxies occurs at the material T K, corresponding to a sharp drop in fracture toughness and ballistic impact performance. Two aliphatic, ring‐opening metathesis polymerized materials are found to exhibit no clear transition from purely ductile to purely brittle behavior, but the temperature dependence is still scaled to a single curve when normalized by T o . The cooperatively rearranging region (CRR) or the volume of this region is related to the breadth of temperatures over which these materials exhibit purely ductile deformation both quasi‐statically and at higher rates. The temperature‐dependent performance is discussed in the context of the configurational entropy. The breadth of the ductility window is related to the size of the CRR, calculated from calorimetric measurements at the resin T g . Published 2019. This article is a U.S. Government work and is in the public domainin the USA. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 511–523 Abstract : The ductile‐to‐brittle transition in polymer networks is investigated at ballistic rates. It is found that the breadth of the temperature window over which these materials exhibit ductile behavior can be estimated from calorimetric measurements. The Vogel temperature and Kauzmann temperature are found to scale the high rate ballistic performance within unique classes of materials. This work provides fundamental insight into how molecular relaxations influence mechanical performance across several orders of magnitude in rate.